Food and nutrition emergencies in East Africa: Political, economic and environmental associations - Oniang’o, Ruth (International Food Policy Research Institute, 2009)
Conflicts have existed for generations worldwide. In sub-Saharan Africa, conflicts occur for various reasons, including inter-tribal or clanist tensions, resource disputes, and externally instigated wars. These conflicts may persist unabated for generations, and can take on different dimensions. When a major conflict breaks out in one country, refugees often move in search of security and basic services (including food), creating major spill-overs that affect the entire region, placing considerable strain on local capacities to manage the food and nutrition needs of local populations and refugees. A sizeable proportion of the land making up sub-Saharan Africa is arid or semi-arid, rendering it unable to sustain livelihoods in any meaningful manner. Furthermore, this region often suffers from political turmoil and poor governance practices. This paper focuses on East Africa, a region that suffers from political, economic and environmental fragility. Few previous papers have examined the detrimental interactions between conflict and economic policy (as represented by reduced resources and limited organizational capacity for public services) in Sub-Saharan Africa nor have many studies examined the traditional coping strategies that sub-Saharan communities may use to resolve conflict. This paper attempts to describe the underlying reasons for the repeated hunger crises on the African continent, particularly in East Africa, followed by a brief analysis of additional factors that may exacerbate such emergencies. One key question is: What can be done to prevent these types of situations, and why haven’t we found a lasting solution? It seems that these problems and their lack of management are largely due to policy failures and lack of political will. In regions of the world that experience earthquakes, hurricanes and typhoons (Africa does not), help may be obtained from outside the country, but the national governments themselves oversee the reconstruction and recovery aspects. In East Africa, in contrast, external assistance is required not only for the immediate disaster response, but also for subsequent development and reconstruction. Why don’t governments in this region prepare for these nearly annual events? Furthermore, given that this is an insecure region, why don’t the governments enact measures aimed at maintaining peace and security, which are necessary for effective development? One means to ensure peace and security in this troubled region is through strategies aimed at enhancing food productivity and access. Furthermore, good governance based on democratic representation of all citizens is key to preventing poverty, hunger, malnutrition, disease and conflict, leading to the attainment of harmony and balance in society.